Commonalities in the Association between PPARG and Vitamin D Related with Obesity and Carcinogenesis. (8th August 2016) - Bandera Merchan, Borja; Tinahones, Francisco José; Macías-González, Manuel
Abstract : The PPAR nuclear receptor family has acquired great relevance in the last decade, which is formed by three different isoforms (PPAR α, PPARβ / δ, and PPAR ϒ ). Those nuclear receptors are members of the steroid receptor superfamily which take part in essential metabolic and life-sustaining actions. Specifically, PPARG has been implicated in the regulation of processes concerning metabolism, inflammation, atherosclerosis, cell differentiation, and proliferation. Thus, a considerable amount of literature has emerged in the last ten years linking PPARG signalling with metabolic conditions such as obesity and diabetes, cardiovascular disease, and, more recently, cancer. This review paper, at crossroads of basic sciences, preclinical, and clinical data, intends to analyse the last research concerning PPARG signalling in obesity and cancer. Afterwards, possible links between four interrelated actors will be established: PPARG, the vitamin D/VDR system, obesity, and cancer, opening up the door to further investigation and new hypothesis in this fascinating area of research.